2021
DOI: 10.1007/s00268-021-05962-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chief Surgeons’ and Assistants’ Feelings of Fatigue Between Laparoendoscopic Single‐site and Conventional Laparoscopic Adrenalectomy

Abstract: Background Our objective was to compare the surgical staff's feelings of fatigue between laparoendoscopic single‐site adrenalectomy (LESS‐A) and conventional laparoscopic adrenalectomy (CLA) before and after surgery. Method Data were collected for surgical procedures performed between June 2011 and September 2017 (57 LESS‐A and 37 CLA). Each procedure in both groups was performed by the same chief surgeon. The subjective fatigue feelings of the key members of the surgical team (chief surgeon, scopist, assistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Additionally, demands on surgical assistants require further investigations because some studies observed less pain and discomfort compared to the primary operating surgeon in both RALS and LS 51 and potentially increased cognitive fatigue. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, demands on surgical assistants require further investigations because some studies observed less pain and discomfort compared to the primary operating surgeon in both RALS and LS 51 and potentially increased cognitive fatigue. 52 …”
Section: Discussionmentioning
confidence: 99%